Covalent Microporous Polymer Nanosheets for Efficient Photocatalytic CO2 Conversion with H2O. Issue 18 (1st April 2022) - Zhi, Qianjun; Zhou, Jun; Liu, Wenbo; Gong, Lei; Liu, Wenping; Liu, Heyuan; Wang, Kang; Jiang, Jianzhuang
Abstract: It is still a challenging target to achieve photocatalytic CO2 conversion to valuable chemicals with H2 O as an electron donor. Herein, 2D imide‐based covalent organic polymer nanosheets (CoPcPDA‐CMP NSs), which integrate cobalt phthalocyanine (CoPc) moiety for reduction half‐reaction and 3, 4, 9, 10‐perylenetetracarboxylic diimide moiety for oxidation half‐reaction, are constructed as a Z‐scheme artificial photosynthesis system to complete the overall CO2 reduction reaction. Owing to the outstanding light absorption capacity, charge separation efficiency, and electronic conductivity, CoPcPDA‐CMP NSs exhibit excellent photocatalytic activity to reduce CO2 to CO using H2 O as a sacrificial agent with a CO production rate of 14.27 µmol g −1 h −1 and a CO selectivity of 92%, which is competitive to the state‐of‐the‐art visible‐light‐driven organic photocatalysts towards the overall CO2 reduction reaction. According to a series of spectroscopy experiments, the authors also verify the photoexcited electron transfer processes in the CoPcPDA‐CMP NSs photocatalytic system, confirming the Z‐scheme photocatalytic mechanism. The present results should be helpful for fabricating high‐performance organic photocatalysts for CO2 conversion. Abstract : 2D imide‐based covalent organic polymer nanosheets (CoPcPDA‐CMP NSs) are fabricated as a Z‐scheme photocatalyst to achieve the overall CO2 reduction reaction with a CO production rate of 14.27 µmol g −1 h −1 and a CO selectivity of 92%.